HOW TO APPLY THE NUMBERED HEAD TOGETHER LEARNING MODEL TO IMPROVE INDONESIAN LEARNING OUTCOMES OF MIDDLE SCHOOL STUDENTS - Firman, Firman; Mirnawati, Mirnawati; Hisbullah, Hisbullah; Usman, Usman; Ramadhana, Muhammad Affan; Harianto, Erwin (Jurnal Riset dan Inovasi Pembelajaran, 2021)
This research is a classroom action research that aims to determine whether the cooperative learning Numbered Head Together (NHT) can improve students’ learning outcome in Indonesian course. The subjects of this study were 45 students of class VII A of SMP Negeri 8 Palopo in the even semester of the 2018/2019 academic year. This research was carried out in two cycles, and each cycle consists of six meetings. Data collection was carried out using learning outcomes tests and observations. The data collected were analyzed using quantitative analysis, and the observation data were analyzed using qualitative analysis. The results showed that the average score of students in the first cycle was 40.02, with a standard deviation of 20.21. while in the second cycle, the average score was 68.26, with a standard deviation of 12.00. It shows that classical student learning outcomes have been achieved. From the results of this study, it can be concluded that with the implementation of cooperative learning NHT in the learning process, the learning outcomes, attendance, readiness, and activeness of students can increase.